2016
DOI: 10.1186/s12864-016-2752-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide copy number variation (CNV) detection in Nelore cattle reveals highly frequent variants in genome regions harboring QTLs affecting production traits

Abstract: BackgroundCopy number variations (CNVs) have been shown to account for substantial portions of observed genomic variation and have been associated with qualitative and quantitative traits and the onset of disease in a number of species. Information from high-resolution studies to detect, characterize and estimate population-specific variant frequencies will facilitate the incorporation of CNVs in genomic studies to identify genes affecting traits of importance.ResultsGenome-wide CNVs were detected in high-dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 95 publications
7
24
0
2
Order By: Relevance
“…Compared with SNP, CNVs are longer fragments of variation with more significant effects on the growth traits of sheep. More and more copy number variation studies have been performed on different species, such as human [24], mouse [25], cattle [26,27], chicken [28], monkey [29], and sheep [30,31]. In recent years, with increasing consumer requirements for sheep quality and the development of molecular breeding, there is a need to exploit CNV molecular genetic variation for economic trait selection and disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with SNP, CNVs are longer fragments of variation with more significant effects on the growth traits of sheep. More and more copy number variation studies have been performed on different species, such as human [24], mouse [25], cattle [26,27], chicken [28], monkey [29], and sheep [30,31]. In recent years, with increasing consumer requirements for sheep quality and the development of molecular breeding, there is a need to exploit CNV molecular genetic variation for economic trait selection and disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…CNV research has been extended to all types of livestock, including chicken [7,8], pig [9,10], goat [11], and sheep [12]. At the same time, more and more people are paying attention to the link between CNV and cattle health and production performance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Single copy duplications (58.9 %) followed by single copy deletions (37.5 %) were the most frequent events in this Nelore population (Table 2). Similarly, Silva et al, [28] observed these two events as the most commons in 1,717 commercially available Nelore semen samples, accounting together for 97.3 % of the CNV calls identified. The distribution of the 2,119 CNVs across the bovine chromosomes is shown in Fig 1. The highest percentage of the CNV calls is located on BTA12 (10.4 %), followed by BTA15 (7.8 %), BTA7 (6.8 %) and BTA10 (6.3 %), harboring together 663 CNVs.…”
Section: Genome-wide Cnv Detectionmentioning
confidence: 68%
“…Presence of both types was observed in 14 regions. Likewise, Santana et al [27] and Silva et al [29] reported more losses than gain and mixed regions, opposing to Silva et al [28] that observed more mixed regions. CNVRs length varied from 7.2 to 2,910.2 kb, with an average of 121.3 kb.…”
Section: Cnv Regions Mapping and Association Analysismentioning
confidence: 90%
See 1 more Smart Citation